VHDL Implementation of H.264 Video Coding Standard - Haresh A. Suthar (Institute of Advanced Engineering and Science, 2012)
This Paper contains VHDL implementation of H.264 video coding standard, which is new video coding standard of the ITU-T Video Coding Experts Group and the ISO/IEC Moving Picture Experts Group. The main goal of the H.264/AVC standardization effort is to enhance compression performance and provision of a “network-friendly” video representation addressing “conversational” (video telephony) and “no conversational” (storage, broadcast, or streaming) applications.H.264 video coder standard is having fundamental blocks like transform and quantization, Intra prediction, Inter prediction and Context Adaptive Variable Length Coding (CAVLC). Each block is designed and integrated to one top module in VHDL.